Why z > 1 radio-loud galaxies are commonly located in protoclusters - Hatch, N.; Wylezalek, D.; Kurk, J.; Stern, D.; Breuck, C.D.; Jarvis., M.; Galametz, A.; Gonzalez, A.; Hartley, W.; Mortlock, A.; Seymour, Nick; Stevens, J. (Oxford University Press, 2014)
Distant powerful radio-loud active galactic nuclei (RLAGN) tend to reside in dense environments and are commonly found in protoclusters at z > 1.3. We examine whether this occurs because RLAGN are hosted by massive galaxies, which preferentially reside in rich environments. We compare the environments of powerful RLAGN at 1.3 < z < 3.2 from the Clusters Around Radio-Loud AGN survey to a sample of radio-quiet galaxies matched in mass and redshift. We find that the environments of RLAGN are significantly denser than those of radio-quiet galaxies, implying that not more than 50 per cent of massive galaxies in this epoch can host powerful radio-loud jets. This is not an observational selection effect as we find no evidence to suggest that it is easier to observe the radio emission when the galaxy resides in a dense environment. We therefore suggest that the dense Mpc-scale environment fosters the formation of a radio jet from an AGN. We show that the number density of potential RLAGN host galaxies is consistent with every >1014 M⊙ cluster having experienced powerful radio-loud feedback of duration ~60 Myr during 1.3 < z < 3.2. This feedback could heat the intracluster medium to the extent of 0.5–1 keV per gas particle, which could limit the amount of gas available for further star formation in the protocluster galaxies.